2023
DOI: 10.1021/jacs.3c08101
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Photolysis of H2O2 at the Air–Water Interface of a Microdroplet

Zepeng Rao,
Ye-Guang Fang,
Yishuai Pan
et al.

Abstract: Photochemical homolysis of hydrogen peroxide (H2O2) occurs widely in nature and is a key source of hydroxyl radicals (·OH). The kinetics of H2O2 photolysis play a pivotal role in determining the efficiency of ·OH production, which is currently mainly investigated in bulk systems. Here, we report considerably accelerated H2O2 photolysis at the air–water interface of microdroplets, with a rate 1.9 × 103 times faster than that in bulk water. Our simulations show that due to the trans quasiplanar conformational pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Molecules located at the water–air interface of aqueous aerosol droplets may show photochemistry that is modified from that in the gas phase, as exemplified by calculations from Francisco and co-workers for hydrogen peroxide (H 2 O 2 ) on a water droplet surface . Because the H 2 O 2 adopts a different geometry at the interface than in the bulk solution or the gas phase, its UV absorption band shifts to longer wavelength and better overlaps the solar spectrum, which accelerates its photolysis by tropospheric solar radiation to produce OH radicals.…”
Section: Theoretical and Computational Atmospheric Photochemistrymentioning
confidence: 99%
“…Molecules located at the water–air interface of aqueous aerosol droplets may show photochemistry that is modified from that in the gas phase, as exemplified by calculations from Francisco and co-workers for hydrogen peroxide (H 2 O 2 ) on a water droplet surface . Because the H 2 O 2 adopts a different geometry at the interface than in the bulk solution or the gas phase, its UV absorption band shifts to longer wavelength and better overlaps the solar spectrum, which accelerates its photolysis by tropospheric solar radiation to produce OH radicals.…”
Section: Theoretical and Computational Atmospheric Photochemistrymentioning
confidence: 99%
“…Few studies have comprehensively addressed the impacts of these reaction environments on surface radicals and their conversion. Notably, various liquid/solid interfacial environments including microdroplets, , poor wettable surface, and hydrophobic surfaces , have demonstrated significant influences on the formation of H 2 O 2 . Therefore, a rigorous examination of the impact of reaction environment on the mechanism and kinetics of H 2 O 2 and O 2 evolution is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies claimed that liquid surfaces, especially water surfaces, may be able to accelerate chemical reactions . For example, Rao et al found that the photolysis rate of H 2 O 2 at the air–water interface of the droplets was greatly accelerated, being 1.9 × 10 3 times faster than that in the aqueous phase. Kusaka et al used ultrafast phase-sensitive interface-selective nonlinear vibration spectroscopy to detect the photochemical reaction at the air–water interface.…”
Section: Introductionmentioning
confidence: 99%